A new genus and species of katydids of the tribe Polyancistrini (Orthoptera: Tettigoniidae: Pseudophyllinae) from Brazil, an apparent pest of Eucalyptus plantations - Naskrecki, Piotr; Lopes-Andrade, Cristiano (Zootaxa, 2005)
A new genus and species of polyancistrine katydid, Spinapecta alieniphaga gen. n. et sp. n. is described from Minas Gerais State, Southeastern Brazil. It is closely related to Polyancistrus Serville, but differs from this and other members of Polayncistrini (Tettigoniidae: Pseudophyllinae) in the unique structure of the male abdomen, sternal armature, and the female sound producing organs. S. alieniphaga appears to be a pest of Eucalyptus plantations.